A six years review of placenta Accreta Spectrum Disorder in a tertiary referral Hospital - Dzulkifli, Izzni Adilah; Ismail, Hamizah; Nusee, Zalina; Mohd Nordin, Noraihan (2021)
A Six Years Review of Placenta Accreta Spectrum Disorder in a Tertiary Referral Hospital Izzni Adilah Dzulkifli1, Hamizah Ismail1, Zalina Nusee1, Noraihan Mohd Nordin2 1 Department of Obstetrics and Gynaecology, International Islamic University Malaysia, Kuantan, Pahang 2Department of Obstetrics and Gynaecology, Hospital Tuanku Azizah Kuala Lumpur Introduction: Placenta Accreta Spectrum results from the rising caesarean sections, hence impacting maternal morbidity and mortality. This research is a review of women with PAS at a single tertiary center from 2015 till 2020.Materials and method: Data from medical records were collected in which women with PAS were categorized according to their primary surgical approach. SPSS version 25.0 was used for descriptive analysis. Results: There were 65 PAS cases with an overall incidence of 1 per 1000 deliveries. Four cases were excluded due to missing records. PAS affected women of age 35.8+/-4.8(36), 85% were multiparous, 96% of the women had previous caesarean delivery in whom 88% had placenta praevia. Thirty-eight had a primary caesarean hysterectomy, 23 had uterine conserving surgery. Fourteen women required delayed hysterectomy due to complications. Prenatal imaging (US/MRI) had a significant association with the intraoperative findings and histopathological confirmation of PAS (p<0.01).Adjunct procedure (internal iliac artery balloon occlusion, uterine artery embolization, uterine artery ligation) on both groups showed no significant effect on the blood loss (p=0.64).Caesarean hysterectomy were associated with higher blood loss, blood transfusions and bladder injury (p<0.05).There was no maternal death in this study. No pregnancy reported in the uterine conserved group. Conclusion: Previous caesarean delivery is the leading risk factor for PAS. Primary caesarean hysterectomy carries higher morbidity. Conservative approach is possible in selected cases through perioperative planning in an established well-equipped center.